2013
DOI: 10.1007/s00586-013-2925-z
|View full text |Cite
|
Sign up to set email alerts
|

Expert’s comment concerning Grand Rounds case entitled “Vertebral artery injury and severely displaced odontoid fracture: the case for early reduction” (by M.P. Sullivan, J.D. McCormick, V. Arlet)

Abstract: This is an interesting case report describing an excellent clinical result achieved by indirect decompression of the vertebral artery by ''early'' reduction with traction in a trans-odontoid atlanto-axial luxation fracture [1]. The trans-odontoid luxation fracture is a highly unstable traumatic lesion of the atlanto-axial complex most often associated with an Anderson type II fracture of the odontoid (Fig. 1). In many cases, this luxation can already be suspected on the conventional X-rays by the position of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Surgical treatment of odontoid luxation fracture remains controversial. Our review of published reports revealed that different authors performed different surgical procedures for type II odontoid fractures associated with posterolateral atlas complete dislocation. In our case, after closed reduction had failed we operated via a posterior approach.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Surgical treatment of odontoid luxation fracture remains controversial. Our review of published reports revealed that different authors performed different surgical procedures for type II odontoid fractures associated with posterolateral atlas complete dislocation. In our case, after closed reduction had failed we operated via a posterior approach.…”
Section: Discussionmentioning
confidence: 78%
“…A search of published reports revealed that type II odontoid fracture combined with atlas posterolateral dislocation is rare, only nine cases with adequate radiography data having been reported thus far; reduction with cervical traction was achieved in only three of eight cases (Table ). Many factors can make reduction of this type of injury difficult, the central factor likely being bilateral interlocking of the atlantoaxial lateral mass joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations